Detection of DNA-recombinant human Epoetin-Alfa as a pharmacological ergogenic aid - Wilber, R. L. (Sports Medicine, 2002)
The use of DNA-recombinant human epoetin-alfa (rhEPO) as a pharmacological ergogenic aid for the enhancement of aerobic performance is estimated to be practised by at least 3 to 7% of elite endurance sport athletes. rhEPO is synthesised from Chinese hamster ovary cells, and is nearly identical biochemically and immunologically to endogenous epoetin-alfa (EPO). In a clinical setting, rhEPO is used to stimulate erythrocyte production in patients with end-stage renal disease and anaemia. A limited number of human studies have suggested that rhEPO provides a significant erythropoietic and ergogenic benefit in trained individuals as evidenced by increments in haemoglobin, haematocrit, maximal oxygen uptake (V-dot(2max)) and exercise endurance time. The purpose of this review is to summarise the various technologies and methodologies currently available for the detection of illicit use of rhEPO in athletes. The International Olympic Committee (IOC) banned the use of rhEPO as an ergogenic aid in 1990. Since then a number of methods have been proposed as potential techniques for detecting the illegal use of rhEPO. Most of these techniques use indirect markers to detect rhEPO in blood samples. These indirect markers include macrocytic hypochromatic erythrocytes and serum soluble transferrin receptor (sTfr) concentration. Another indirect technique uses a combination of 5 markers of enhanced erythropoiesis (haematocrit, reticulocyte haematocrit, percentage of macrocytic red blood cells, serum EPO, sTfr) to detect rhEPO. The electrophoretic mobility technique provides a direct measurement of urine and serum levels of rhEPO, and is based on the principle that the rhEPO molecule is less negatively charged versus the endogenous EPO molecule. Isoelectric patterning/focusing has emerged recently as a potential method for the direct analysis of rhEPO in urine. Among these various methodologies, the indirect technique that utilises multiple markers of enhanced erythropoiesis appears to be the most valid, reliable and feasible protocol currently available for the detection of rhEPO in athletes. In August 2000, the IOC Medical Commission approved this protocol known as the 'ON model', and it was subsequently used in combination with a second, confirmatory test (isoelectric patterning) to detect rhEPO abusers competing in the 2000 Sydney Summer Olympics. This combined blood and urine test was approved with modifications by the IOC in November 2001 for use in the 2002 Salt Lake City Winter Olympics.